Cytologically confirmed splenic metastases in breast cancer. (November 2012) - Bartolotti, Marco; Franceschi, Enrico; Battista, Monica Di; Esposti, Roberta Degli; Castaldini, Luciano; Baccarini, Paola; Brandes, Alba Ariela
Relatively few cases of splenic metastases have been reported in the literature. Metastases to the spleen generally occur in the context of multivisceral involvement during the late stage of disease, while isolated splenic metastases are far less frequent. The primary cancer types commonly leading to splenic metastases are skin melanoma and gynecologic, colorectal and gastric cancers. Breast cancer is considered a rare source of splenic metastases, with few cases being reported in the literature. As a contribution to the literature, we report here on a case of splenic metastasis in a patient with breast cancer treated at the Department of Medical Oncology at our institution (Bellaria-Maggiore Hospital, Azienda USL of Bologna, Italy).